Microglia‐mediated phagocytosis of apoptotic nuclei is impaired in the adult murine hippocampus after stroke. Issue 8 (4th May 2021) - Rudolph, Max; Schmeer, Christian W.; Günther, Madlen; Woitke, Florus; Kathner‐Schaffert, Carolin; Karapetow, Lina; Lindner, Julia; Lehmann, Thomas; Jirikowski, Gustav; Witte, Otto W.; Redecker, Christoph; Keiner, Silke
Abstract: Following stroke, neuronal death takes place both in the infarct region and in brain areas distal to the lesion site including the hippocampus. The hippocampus is critically involved in learning and memory processes and continuously generates new neurons. Dysregulation of adult neurogenesis may be associated with cognitive decline after a stroke lesion. In particular, proliferation of precursor cells and the formation of new neurons are increased after lesion. Within the first week, many new precursor cells die during development. How dying precursors are removed from the hippocampus and to what extent phagocytosis takes place after stroke is still not clear. Here, we evaluated the effect of a prefrontal stroke lesion on the phagocytic activity of microglia in the dentate gyrus (DG) of the hippocampus. Three‐months‐old C57BL/6J mice were injected once with the proliferation marker BrdU (250 mg/kg) 6 hr after a middle cerebral artery occlusion or sham surgery. The number of apoptotic cells and the phagocytic capacity of the microglia were evaluated by means of immunohistochemistry, confocal microscopy, and 3D‐reconstructions. We found a transient but significant increase in the number of apoptotic cells in the DG early after stroke, associated with impaired removal by microglia. Interestingly, phagocytosis of newly generated precursor cells was not affected. Our study shows that a prefrontal stroke lesion affects phagocytosis of apoptotic cells in the DG, a region distal to the lesion core. Whether disturbed phagocytosis might contribute to inflammatory‐ and maladaptive processes including cognitive impairment following stroke needs to be further investigated. MAIN POINTS: Stroke reduces the number of phagocytic microglia in the dentate gyrus Reduced microglia phagocytosis leads to a transient overload of apoptotic cells Post‐lesional microglial phagocytosis of newly born cell is not affected